Tanjung Datu National Park, Sarawak: Communities’ Perceptions towards Its Rural Competitive Advantage - Lo, May-Chiun; Cheuk, Sharon; Azuriaty, Atang (Canadian Center of Science and Education, 2015)
Rural tourism is a rapidly growing tourism segment and has been given increasing importance, in view of its potential to contribute economic growth to the rural areas. However, any rural tourism destination development should be implemented in a way that maximizes destination competitive advantage. This study examine the relationship between stakeholder involvement, community knowledge about tourism, and the economic, socio-cultural and environmental impacts on tourism with rural competitive advantage, as perceived by the local community. This study obtained, as voluntary respondents, 87 residents of a rural tourism destination in Sarawak, Malaysia. To assess the developed model, SmartPLS 2.0 (M3) was applied based on path modelling and then bootstrapping with 200 re-samples was applied to generate the standard error of the estimate and t-values. The findings suggested that stakeholder involvement in tourism, community knowledge about tourism and the environmental impact of tourism have had a significant positive impact on rural competitive advantage, whereas economic and socio-cultural impacts of tourism, as well as community support for tourism, had little impact on the same. Lastly, such study would benefit the tourism implementers and decision-makers in tourism industry, in the sense that tourism activity can be proactively detected and curbed once critical mass is reached.